Translating The Visual Representations to The Symbolic For Solving Mathematic Problems - Hanifah Hanifah; S B Waluya; Isnarto Isnarto; M Asikin (Universitas Negeri Semarang, 2021)
This study aims to analyze the ability to translate visual representations into symbolic representations in solving mathematical problems. This research is a descriptive research with a qualitative approach. The subjects in this study were students with high, medium and low mathematical abilities. Data collection techniques were carried out by giving tests and interviews. The results showed that the S-H subject met the Unpacking the Source indicator, while the S-M and M-L subjects did not meet the indicator. In Preliminary coordination, S-H subjects and S-M subjects have met these indicators, while for M-L subjects have not fulfilled them. In Constructing the Target, subjects S-H and subject S-M have met these indicators, for subjects M-L have not been able to fulfill them. In Determining Equivalence, subjects S-H and subject S-M have met these indicators, while for subjects M-L have not fulfilled. So that the conclusion obtained is that the S-H subject has fulfilled all translation indicators between visual representations to symbolic representations, while S-M subjects are only Unpacking the Source indicators that do not meet and for M-L subjects all translation indicators between visual representations to symbolic representations are not fulfilled.